Binder-Free Charantia-Like Metal-Oxide Core/Shell Nanotube Arrays for High-Performance Lithium-Ion Anodes - Xu, Pingping; Zhang, Ziying; Zhang, Huizhen; Shen, Ao; Zhao, Yangqiang; Zhou, Yangyang; Weng, Ying (Frontiers in Chemistry, 2020)
The high performance of lithium-ion anodes relies largely on a scrupulous construction of nano-architectures and smart hybridization of the bespoke active materials. We present a powerful two-step seed-free solution-based method for the fabrication of the binder-free hierarchical charantia-like TiO2/Fe2O3 hollow core/shell nano-arrays, which were directly grown on carbon cloth substrates with ultrahigh mass-loading. The three-dimensional porous hollow architecture and the direct contact to CC current collector ensure an efficient electronic pathway. The carambola-like TiO2 hollow framework effectively protects the hierarchical charantia-like TiO2/Fe2O3 hollow core/shell arrays from collapse for its negligible volume change upon cycling, while the self-assembled α-Fe2O3 hollow nano-spheres guarantee a large capacity and high contact area with electrolyte. The electrochemical measurements demonstrate that this flexible three-dimensional binder-free porous charantia-like hollow architecture exhibits remarkably good cycle performance, high reversible capacity, and excellent rate capability. The charantia-like CC/TiO2/Fe2O3 hollow nano-arrays still maintain a high reversible capacity of 875 mAh g-1 after 200 cycles at 200 mAg-1. The facile, cost-effective, and scalable fabrication strategy has broad prospects in the implementation of the wearable high-performance energy storage devices.